Harvesting in an integrated general equilibrium model - Thomas Eichner; Rüdiger Pethig (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2007)
Harvesting of prey biomass is analyzed in an integrated ecological-economic system whose submodels, a predator-prey ecosystem and a simple economy, are microfounded dynamic general equilibrium models. These submodels are interdependent because the ecosystem responds to harvesting - through the reactions of optimizing individual organisms - by changing the provision of public ecosystem services to consumers. General analytical results are derived regarding the impact of harvesting policies on short-run equilibria of both submodels, on population dynamics, and on stationary states of the integrated model. A key insight is that prey biomass carries a positive ecosystem price which needs to be added as a tax mark-up to the economic price of harvested biomass to attain allocative efficiency. Further information on the dynamics is gained by resorting to numerical analysis of the policy regimes of zero harvesting, laissez-faire harvesting and efficient harvesting.
Keywords: Q20; Q57; 330; predator; prey; biomass price; harvesting; Bioenergie; Allgemeines Gleichgewicht; Ressourcenökonomik; Fischereiressourcen